2005
DOI: 10.5194/acpd-5-8421-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrocarbon-like and oxygenated organic aerosols in Pittsburgh: insights into sources and processes of organic aerosols

Abstract: Abstract. A recently developed algorithm (Zhang et al., 2005) has been applied to deconvolve the mass spectra of organic aerosols acquired with the Aerosol Mass Spectrometer (AMS) in Pittsburgh during September 2002. The results are used here to characterize the mass concentrations, size distributions, and mass spectra of hydrocarbon-like and oxygenated organic aerosol (HOA and OOA, respectively). HOA accounts for 34% of the measured organic aerosol mass and OOA accounts for 66%. The mass concentrations of HOA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
193
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(228 citation statements)
references
References 39 publications
30
193
3
2
Order By: Relevance
“…For comparison purposes, m/z 28 and 18 were removed from the soil/litter and ponderosa pine SOA UMR spectra since they had been omitted from the reference α-pinene SOA spectra due to known complications attributing the appropriate fraction of these peaks to the organic aerosol component. 49,50 All three UMR organic spectra were similar with slopes between 0.95 and 1.09 and r 2 values ≥0.86 for all three comparisons (the comparisons included all m/z 12−195 except m/z 18 and 28). Of particular note, SOA generated from the soil/litter emissions and from live ponderosa pine were nearly identical (r 2 = 0.98, slope = 0.95).…”
Section: Environmental Science and Technologymentioning
confidence: 79%
“…For comparison purposes, m/z 28 and 18 were removed from the soil/litter and ponderosa pine SOA UMR spectra since they had been omitted from the reference α-pinene SOA spectra due to known complications attributing the appropriate fraction of these peaks to the organic aerosol component. 49,50 All three UMR organic spectra were similar with slopes between 0.95 and 1.09 and r 2 values ≥0.86 for all three comparisons (the comparisons included all m/z 12−195 except m/z 18 and 28). Of particular note, SOA generated from the soil/litter emissions and from live ponderosa pine were nearly identical (r 2 = 0.98, slope = 0.95).…”
Section: Environmental Science and Technologymentioning
confidence: 79%
“…Figure 1A summarizes observed ∆OA/∆CO enhancement ratios from different studies that were influenced by urban emissions. Red lines are estimates of emission ratios (POA) (7,12,13,(22)(23)(24)(25); blue lines were obtained in aged air (POA + SOA) (7,9,(17)(18)(19)22). These results were determined from field studies on three continents and indicate that the ∆OA/∆CO ratios in aged urban air are systematically higher.…”
Section: Urban Sourcesmentioning
confidence: 96%
“…In this feature article, we briefly review the latest insights from field studies into the sources of organic aerosol (OA). Many results were obtained using two relatively new methods for quantifying OA on time scales of minutes: particle-into-liquid sampling combined with total organic carbon analysis for measurements of water-soluble organic carbon (5) and aerosol mass spectrometry (AMS) (6); both have been evaluated in detail against other reported methods, both in terms of the mass loading (7)(8)(9)(10) as well as the source apportionment (11)(12)(13) of organic aerosol.…”
mentioning
confidence: 99%
“…Note that N(D va ) is a lower limit particle number concentration for particles in the 40 to 1000 nm D va range due to decreased inlet transmission outside of the 60 to 600 nm range. Values for r were estimated based on a weighted average calculation using mass concentrations measured by the Q-AMS [Zhang et al, 2005] by…”
Section: Event Definitionmentioning
confidence: 99%
“…Using an Aerodyne quadrupole aerosol mass spectrometer (Q-AMS), organic compounds were identified as the major constituent of sub-100 nm diameter aerosol following new particle formation events at a forested site in southern Finland [Allan et al, 2006]. In a more polluted atmosphere near Pittsburgh, PA, ammonium and sulfate contributed the majority of condensable mass during the early stages of growth events; however, photochemically produced secondary organic aerosol (SOA) contributed significantly to growth during later stages of these events [Zhang et al, 2004[Zhang et al, , 2005. In contrast, Hock et al [2008] observed a growth event in rural southern Germany with significant mass contribution from aerosol nitrate.…”
Section: Introductionmentioning
confidence: 99%